Analisis Pelaksanaan Pelatihan Karyawan Air Traffic Flow Management Dalam Meningkatkan Pelayanan Penerbangan Di Kantor Airnav Cabang Surabaya - Adella Anggelica Pramudita Santoso; Dodi R Setiawan (Jurnal Ilmu Administrasi Publik, 2023)
The background of this study was the writer’s observation regarding the Implementation of Air Traffic Flow Management Employee Training at the Surabaya Branch of Airnav. According to the research, Analysis of the Implementation of Air Traffic Flow Management Employee Training in Improving Aviation Services at the Surabaya Branch of Airnav has not been well executed so that it can be said not effective. This study aimed to identify the Implementation of Air Traffic Flow Management Employee Training in Improving Aviation Services at the Surabaya Branch of Airnav, so the Air Traffic Flow Management employees get training that is in accordance with the needs of employees and organizations. The qualitative method was used for this study, using 2 leaders, 2 staff and 1 academician as the population. Total sampling was used for the data sampling technique, which was taking the entire population to be used as samples, namely 2 leaders, 2 staff and 1 academician. For the data collection, the writer chose to use observation, interviews and documentation. The results of research at Air Traffic Flow Management at the Airnav Office Surabaya Branch based on the interviews and observations methods indicated that the implementation of training for Air Traffic Flow Management Employees in Improving Flight Services at the Airnav Office Surabaya Branch has not been said to be effective because there were several inhibiting factors, one of which was that Air Traffic Flow Management personnel have not been declared as flight personnel.